Active rock glaciers and the lower limit of discontinuous alpine permafrost, Khumbu Himalaya, Nepal - Matthias Jakob (Permafrost and Periglacial Processes)
Seismic refraction studies were carried out on four rock glaciers in the Khumbu Himalaya near the Poklade massif (27°55′ N, 86°50′ E) and its surroundings. P‐wave velocities at profiles on southeast‐facing slopes indicate that the lower limit of discontinuous alpine permafrost is between 5560 m and 5360 m a.s.l. On west‐facing slopes the lower limit varies between 4959 m and 5050 m a.s.l. These values agree with elevations of active rock glacier termini. Des études par réfraction séismique ont été réalisées sur quatre glaciers rocheux dans l'Himalaya Khimbu, à proximité du massif Poklade (27°55′N, 86°50′E). Les vitessses des ondes primaires suivant des profils réalisés sur des pentes exposées au sud‐est indiquent que la limite inférieure du pergélisol de montagne se situe entre 5560 et 5360 m d'altitude. Ces valeurs correspondent bien aux extrémités des glaciers rocheux actifs.